Review: Biogas Production from Rice Husks - Astria, Windi; Putri, Ratih Ramadhani; Fattah, Hanif Al; Suhendi, Endang; Syaichurrozi, Iqbal (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
For Indonesians, rice is a basic diet. Rice husks, a waste product of the milling process used to turn paddy into rice, have a great potential for conversion into raw materials for biogas. Several factors that affect the rate of biogas production are the initial treatment (pre-treatment), temperature, acidity (pH), total solid content (TS), and C/N ratio, this is done to help the degradation process of lignin and cellulose can run quickly which has an impact on increasing biogas production. The development of biogas from rice husk waste has significant promise for Indonesia since it can help reduce the country's rice husk waste stockpile and could eventually become one of the country's primary alternative energy sources.